Lessons learned from China's response to coronavirus disease 2019 pandemic and implications for the rest of the world - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Wolters Kluwer Medknow Publications, 2020)
The coronavirus disease-2019 (COVID-19) outbreak, which started from a single city in China has been designated as a public health emergency of international concern. Despite being the most affected nation for close to 2 months, the situation has reversed in China and at present, the nation accounts for only 1% of global caseload and 1% of global deaths. All these estimates are very much suggestive that China has been successful in containing the outbreak in their settings. However, it will not be wise to expect that the outbreak is totally under control as long as the pandemic is going on. The most important lesson from the containment efforts in China was that a single approach will not be right in all the settings. In conclusion, China has been successful in containing the COVID-19 infection and the experience from China should be utilized by other nations who are fighting against the infection. On the contrary, China should not be relaxed and prepare themselves for a fresh wave of infection and also address the special needs during the recovery phase of the disease.